Internalisasi Nilai-Nilai Moderasi Beragama Melalui Pembelajaran Pendidikan Agama Islam di SMA PGRI 2 Jombang - Nisa, Khoirun; Waqfin, Mohammad Saat Ibnu; Wafa, M Aliyul (JoEMS (Journal of Education and Management Studies), 2023)
There are many cases of intolerance both in the form of radicalism that occur in educational institutions, especially in high schools in Indonesia, so it is very necessary to have a solution that creates an atmosphere of harmony in carrying out state and religious life with religious moderation. Schools are the main arena in upholding Pancasila values and religious moderation. Therefore the right solution to reinforce these values so that they can be used as guidelines in teaching and learning activities is through Islamic Religious Education. The approach taken in this study uses qualitative research methods, namely research that departs from inductive thinking patterns, which are based on participatory objective observations of a social phenomenon. The phenomenon in question includes past, present and even future conditions. The internalization of religious moderation values ​​through PAI learning at SMA PGRI 2 has been implemented, namely planning for internalizing religious moderation values ​​through PAI learning at SMA PGRI 2 is coordination between schools and education stakeholders, forming programs according to the school curriculum, outreach, planning PAI learning tools and morning greetings.